2008
DOI: 10.1038/nm1744
|View full text |Cite
|
Sign up to set email alerts
|

Drug-induced cure drives conversion to a stable and protective CD8+ T central memory response in chronic Chagas disease

Abstract: In this study, we document the development of stable, antigen-independent CD8+ T cell memory after drug-induced cure of a chronic infection. By establishing a system for drug cure of chronic Trypanosoma cruzi infection, we present the first extensively documented case of total parasite clearance after drug treatment of this infection. Cure resulted in the emergence of a stable, parasite-specific CD8+ T cell population with the characteristics of central memory cells, based upon expression of CD62L, CCR7, CD127… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
200
0
4

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(219 citation statements)
references
References 48 publications
15
200
0
4
Order By: Relevance
“…In the same way, Caldas et al (Caldas et al, 2008) observed a significant decrease in parasite load in mice treated with Bz during the acute phase of infection, without effect on chronic cardiac lesions. Whereas, Bustamante et al (Bustamante et al, 2008) showed that when Bz is administered for 40 days, parasitological cure and stable and protective CD8+ T central memory response are obtained. Furthermore, Bz itself can modulate the immune response during indeterminate and chronic Chagas disease (Sathler-Avelar et al, 2008;SathlerAvelar et al, 2009).…”
Section: Role Of Anti-chagasic Therapy In the Chronic Cardiomiopathymentioning
confidence: 98%
See 1 more Smart Citation
“…In the same way, Caldas et al (Caldas et al, 2008) observed a significant decrease in parasite load in mice treated with Bz during the acute phase of infection, without effect on chronic cardiac lesions. Whereas, Bustamante et al (Bustamante et al, 2008) showed that when Bz is administered for 40 days, parasitological cure and stable and protective CD8+ T central memory response are obtained. Furthermore, Bz itself can modulate the immune response during indeterminate and chronic Chagas disease (Sathler-Avelar et al, 2008;SathlerAvelar et al, 2009).…”
Section: Role Of Anti-chagasic Therapy In the Chronic Cardiomiopathymentioning
confidence: 98%
“…This can be done through sensitive methods such as immunohistochemistry, polymerase chain reaction (PCR), and in situ hybridization (Britto, 2009;Deborggraeve et al, 2009;Duffy et al, 2009;Rassi et al, 2009a;Rassi and Rassi, 2009;Rassi et al, 2009c). Experimentally, this is demonstrated by attenuation of cardiomyopathy with parasite load reduction by trypanocidal treatment (Britto, 2009;Bustamante et al, 2008;Coura, 2009;Marin-Neto et al, 2009;Perez-Molina et al, 2009;Urbina, 2009b;Viotti et al, 2009). However, myocardial inflammatory infiltrates and lesions are not uniformly reduced in mice infected with different T. cruzi strains and treated with benznidazole (Bz) (Caldas et al, 2008;MarinNeto et al, 2009;Rassi and Rassi, 2009).…”
Section: Myocardial Damage Directly Related To Parasite Persistencementioning
confidence: 99%
“…PCR was identified as one of the necessary criteria because it is more sensitive and time efficient than haemoculture (Camandaroba et al 2003, Caldas et al 2008a, Miyamoto et al 2008) and it reduces the technicians' levels of exposure to the parasite. The use of cyclophosphamide to enhance the sensitivity of the parasitological cure analysis was also discussed because immunosuppressed animals that experience therapeutic failure quickly recover their high levels of parasitaemia (Bustamante et al 2008, Santos et al 2008.…”
Section: For In Vitro Models For Chagas Disease Drug Discovery and Dementioning
confidence: 99%
“…The reasons for the marked difference in the antiparasitic efficacy of nitro-heterocyclic compounds in the acute and chronic stages of the disease are unclear (Cançado 2002), but they may be related to unfavourable pharmacokinetic properties, such as relatively short half-lives and limited tissue penetration (Raaflaub & Ziegler 1979, Raaflaub 1980, Workman et al 1984, which will limit their action in the chronic stage when the parasites are mostly confined in deep tissues and undergo slow replication (Urbina 1999a, Urbina & Docampo 2003. In any case, verifying a true parasitological cure in chronic infection, where the levels of circulating parasites can be extremely low or undetectable even with the most sensitive PCR methods available (Martins et al 2008), remains an extremely challenging problem that requires developing other criteria, such as immunological assays that measure T-cell responses to drug treatment (Bustamante et al 2008).…”
Section: Relevance Of Specific Chemotherapy For Chagas Disease and LImentioning
confidence: 99%